Commitment to Equity Handbook Estimating the Impact of Fiscal Policy on Inequality and Poverty - Lustig, Nora (Brookings Institution Press, 2018)
A how-to guide for assessing the impact of fiscal policy on inequality and povertyInequality has emerged in recent years as a major topic of economic and political discussion, but it is often unclear whether governments can or should do something about it, and if so, what that something might be. This unique volume, edited by Nora Lustig, an equity expert at Tulane University, helps fill that void. Developed by the Commitment to Equity Institute at Tulane, the book examines both the theory and the practical methods for determining the impact of taxation and public spending on inequality and poverty. It provides a step-by-step guide for policymakers, economists, and social planners when analyzing whether fiscal policy has narrowed or widened inequality. The book also has user-written software for conducting a Commitment to Equity Assessment, along with several country studies of these assessments.In addition to serving as a manual, the book can be used as a stand-alone reference for those interested in the methods for assessing the impact on equity of fiscal policy. It also serves as a textbook for advanced undergraduate and graduate courses on public finance and income distribution.